EFEKTIFITAS METODE OUTDOOR-STUDY DALAM UPAYA MENINGKATKAN MOTIVASI BELAJAR PKN SISWA IX-D MTSN 01 KEPAHING - Armizah Armizah (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2019)
Learning is complicated process which is influenced by some factors, internal and external factors. The internal factor that is faced by the student in IX D class at MTsN 01 Kepahiang academic year 2018/2019 is low of motivation on learning. Motivation is a main factor in a process of learning because high motivation will increase the result of the study. Beside that, various methods of learning is also needed. One of method that can be used in the class is outdoor study. The research is action research by using two cycles of study, the subject is IX D students of MTsN 01 Kepahiang with total number 31 students. The research is descriptive study, the aim of research is to describe the increasing student’s motivation on learning and student’s understanding on PKn subject. The result of the research showed that outdoor study method is effective to increase student’s motivation.